Synthesis and Antiproliferative Activity of Some Dihydro-1H-furo[2,3-c]pyrazole-Flavone Hybrids - Tangeti, Venkata Swamy; Vasundhara, D.; Satyanarayana, K.V.V.V.; Pavan Kumar, Kaja Srinivas (Asian Journal of Chemistry, 2017)
A new series of dihydro-1H-furo[2,3-c]pyrazole-flavone hybrids were synthesized from one-pot four-component reaction of b-keto ester (1), hydrazine (2), 7-hydroxy 8-formyl flavones (3), pyridiniumylide (4) in presence of NEt3 as catalyst under ethanol reflux conditions and their antiproliferative properties were evaluated against human cancer cell lines, namely, laryngeal carcinoma (Hep2), lung adenocarcinoma (A549) and cervical cancer (HeLa). The best among them, furo[2,3-c]pyrazole-flavone with C4'-methoxy substitution was selected for further structure activity relationship (SAR) studies. Among the derivatives, (4S,5S)-ethyl 4-(7-hydroxy-5-methoxy-4-oxo-2-(2,4,6-trimethoxyphenyl)-4H-chromen-8-yl)-3-methyl-4,5-dihydro-1H-furo[2,3-c]pyrazole-5-carboxylate (8r) showed most potent cytotoxic activity against all three cancer cell lines. Toxicity studies revealed that the dihydro-1H-furo[2,3-c]pyrazole-flavones are specifically target the cancer cell lines.